LONGFELLO–BUNIN–TUMANYAN: "THE SONG OF HIAWATHA". - GONCHAR, NATALYA (Bulletin of Yerevan University H: Russian Philology, 2019)
The paper is devoted to one of the best translations by H. Tumanyan, the fragment from Longfellow’s The Song of Hiawatha. It illustrates in details for the first time the premises, motives and circumstances which affected the poet’s decision to initiate this translation. The paper also describes the connection with one of the masterpieces of the Russian translation art: Hiawatha by Ivan Bunin, as well as the features and principles of Tumanyan’s activity as a translator of works of art.